Assessment of water quality using the Overall Index of Pollution and Comprehensive Pollution Index at the upper stretch of River Ganga: Pollution indices of River Ganga - Das, Basanta Kumar; Mishra, Sandeep Kumar; Kumar, Jeetendra; Alam, Absar; Jha, Dharm Nath; Shukla Das , Shyamal Chandra; Thakur, Venkatesh; Verma, Sushil Kumar; Singh, Upendra; Om Verma, Hari; Pandey, Amit Ranjan; Kumar, Vijay (Journal of the Inland Fisheries Society of India, 2023)
Overall Index of Pollution (OIP) and Comprehensive Pollution Index (CPI) are useful tools for assessing the consistency of surface water. A three-year (2017 to 2019) study was carried out using the OIP and CPI to assess the seasonal variation and pollution status of the upper stretch (Harshil, Tehri & Haridwar) of the River Ganga in India. Data obtained from the sample analysis showed that during all seasons, the OIP value of water quality was found to be excellent (OIP